Crystal structure of dicyclohexylammonium N-phthaloylglycinate - Weng, Ng Seik (Malaysian Journal of Science, 1995)
Hydrogen bonds link the dicyclohexylammonium cations to the N-phthaloylglycinato anions in crystalline dicyclohexylammonium N-phthaloylglycinate to give rise to a linear chain structure. Crystals belong to the triclinic PI space group, with a = 8.9837 (8), b = 9.6253 (7), c = 12.3863 (7) Ã…, = 100.029 (5), p = 93.394 (6), 90.411 (7)0